Incorporação de borracha de pneu em misturas asfálticas de diferentes granulometrias (Processos úmido e seco) - Pinheiro, Jorge Henrique Magalhães (2004)
It is estimated that Brazil has approximately 100 million waste tires and scrap over 45 million more every year. The recent #258 resolution by the Brazilian National Environment Council (CONAMA) makes tire recycling mandatory for producers. In 2005, a proportion of 4 to 5 tires will should be recycled so as to decrease the existing number of scrap tires in the environment. In order to contribute for the solution of this problem, as well as to enhance the properties of pavement surfaces, this study presents an investigation of the design and mechanical characterization of asphalt mixes with crumb rubber from tires incorporated in the binder or directly in the mixture, wet and dry process respectively. The research still shows an aggregate analysis of the most commons gradations used with Asphalt-Rubber mixtures, standing out the peculiarity of each mixture, and the construct of two test sections using Asphalt-Rubber. Several contents and gradations of rubber plus different temperatures and digestion time were considerate in the wet process and the results were compared with a commercial Asphalt-Rubber binder performance. Different rubber gradations and the effect of the interaction time were studied in the dry process. Regarding the aggregate gradation analysis, four different gradations were compared, including dense grade, gap grade and open grade frictions course. The results indicate the importance of the digestion time for the dry process and a decrease in the tensile strength, resilient modulus and an increase in the fatigue life for low stress levels for the mixtures with rubber when compared to a conventional mixture. Regarding the aggregate gradations, the gap grade mixtures show higher performance than the dense grade, when the 20% rubber amount was used. Nevertheless the dense grade mixtures have their performance increased with a less viscous Asphalt-Rubber binder. On the other hand, the open grade mixtures had the best behavior with high viscous Asphalt-Rubber, when the binder increased the mixture cohesive properties.